Extending treatment criteria for Barrett’s neoplasia: results of a nationwide cohort of 138 endoscopic submucosal dissection procedures - van Munster, Sanne N.; Verheij, Eva P. D.; Nieuwenhuis, Esther A.; Offerhaus, Johan G. J. A.; Meijer, Sybren L.; Brosens, Lodewijk A. A.; Weusten, Bas L. A. M.; Alkhalaf, Alaa; Schenk, Ed B. E.; Schoon, Erik J.; Curvers, Wouter L.; van Tilburg, Laurelle; van de Ven, Steffi E. M.; Tang, Thjon J.; Nagengast, Wouter B.; Houben, Martin H. M. G.; Seldenrijk, Kees C. A.; Bergman, Jacques J. G. H. M.; Koch, Arjun D.; Pouw, Roos E.; on behalf of the Dutch Barrett Expert Centers (Endoscopy, 2022)
Background The use of endoscopic submucosal dissection (ESD) is gradually expanding for treatment of neoplasia in Barrett’s esophagus (BE). We aimed to report outcomes of all ESDs for BE neoplasia performed in the Netherlands.Methods Retrospective assessment of outcomes, using treatment and follow-up data from a joint database.Results 130/138 patients had complete ESDs, with 126/130 (97 %) en bloc resections. Median (interquartile range (IQR)) procedure time was 121 minutes (90–180). Pathology findings were high grade dysplasia (HGD) (5 %) or esophageal adenocarcinoma (EAC) T1a (43 %) or T1b (52 %; 19 % sm1, 33 % ≥ sm2). Among resections of HGD or T1a EAC lesions, 87 % (95 %CI 75 %–92 %) were both en bloc and R0; the corresponding value for T1b EAC lesions was 49 % (36 %–60 %). Among R1 resections, 10/34 (29 %) showed residual cancer, all detected at first endoscopic follow-up. The remaining 24 patients (71 %) showed no residual neoplasia. Six of these patients underwent surgery with no residual tumor; the remaining 18 underwent endoscopic follow-up during median 31 months with 1 local recurrence (annual recurrence rate 2 %). Among R0 resections, annual local recurrence rate during median 27 months was 0.5 %.Conclusion In expert hands, ESD allows safe removal of bulky intraluminal neoplasia and submucosal cancer. ESD of the latter showed R1 resection margins in 50 %, yet only one third had persisting neoplasia at follow-up. To better stratify R1 patients with an indication for additional surgery, repeat endoscopy after healing of the ESD might be a helpful possible prognostic factor for residual cancer.